Investigating the Effective Factors to Prolongation Time of Employees' Administrative Violations in The Ministry of Health and Medical Education: A Qualitative Research - Farhad Habibi nodeh; Abolfazl Roozbeh; Serajedin Grey; Ghasem Rajabi Vasokolaee; Mohammad Panahi Tosanloo; Bahman Khosravi (Tehran University of Medical Sciences, 2018)
Background: Administrative violations are a person-centered behavior that violates the accepted organizational norms, and thus, can threaten the organization health. Therefore, the present study aimed to identify the causes of prolonging the time of taken to deal with administrative violations were at the staff of Ministry of Health and Medical Education.   Materials and Methods: This study was a qualitative content analysis one. For sampling, convenience, purposeful and snowball sampling methods were used. The sample size continued to saturate the interview data with each group of people. Data collection was performed with open questions and interviews using semi-structured interviews. Finally, all interviews were analyzed using MAXQDA software.   Results: After implementing and data analysis, the causes for prolonging the time spent on administrative violations in primary and recruiting boards were divided into five main categories including "member characteristics"; "actual proceedings"; "Inevitable factors"; " legal factors "and" organizational factors".   Conclusion: According to the findings and experts' opinions, the most problems in the process of handling administrative violations are related to the time lag in the notification process, investigation and expertise. Membership training, teamwork, and the use of members with different expertise can prevent employees from handling administrative offenses.